PENGARUH PENGGUNAAN METODE CONCEPT MAPPING TERHADAP HASIL BELAJAR SISWA KELAS IV SEKOLAH DASAR PADA MATERI JENIS-JENIS PEKERJAAN - Resa Junias Putra (Inculco Journal of Christian Education, 2021)
The background of this research study is because of the low student learning outcomes, especially on the material types of work. This can be seen from the number of students who do not understand the material types of work. Many of the students are still confused about the type of work that produces goods and services. In fact, many of the students get low grades. Seeing this, the researchers tried to provide solutions to the student's problems by using the concept mapping method on the learning outcomes of fourth grade elementary school students regarding the types of work. This research is an experimental quantitative study with a posttest-only control design.This study used two classes, namely the experimental class and the control class with different treatments. This study aims to determine the effect of using the concept mapping method on the learning outcomes of fourth grade elementary school students regarding the types of work. The number of students in this study were all fourth grade students consisting of two classes, namely class IV B as the experimental class, totaling 29 students and class IV A as the control class, totaling 31 students, the total population was 60 students.The results of research using the concept mapping method on student learning outcomes in the subject of types of work indicate a change in the average score of students. The average score of the students in the experimental class given the concept mapping method was higher than the average score for the control class given the lecture treatment. This shows that the concept mapping method has an effect on the learning outcomes of fourth grade students.